AB0435 Effects of Prior Use of BIOLOGICS on the Safety and Effectiveness of Abatacept Administered with or without Methotrexate in Japanese Patients with Rheumatoid Arthritis: Sub-Analysis of the Abatacept All-Cases Post-Marketing Surveillance. (10th June 2014) - Harigai, M.; Ishiguro, N.; Inokuma, S.; Mimori, T.; Ryu, J.; Takasaki, Y.; Takei, S.; Takeuchi, T.; Tanaka, Y.; Yamanaka, H.; Watanabe, M.; Koike, T.
Abstract : Background: The result of post-marketing surveillance (PMS) of 3985 patients reported previously 1 indicated that prior use of biologics, with or without concomitant methotrexate (MTX), was associated with the safety and effectiveness of ABT. Objectives: To assess the independent effects of prior biologic therapy and concomitant MTX on the safety and effectiveness of ABT in a sub-analysis of the Japanese PMS data. Methods: ABT-naïve patients who were registered and observed for 24 weeks in the PMS were first divided into subgroups according to concomitant MTX (MTX+ vs MTX−) and then subdivided into biologic-naïve and -experienced groups. Safety and effectiveness were analysed in each subgroup. Disease Activity Score (DAS) 28 (C-reactive protein [CRP]) was calculated at baseline, weeks 4, 12 and 24. Multivariate logistic regression analyses of safety and effectiveness were performed. Results: The MTX− group included 321 biologic-naïve and 986 biologic-experienced patients (mean age: 65.4 vs 64.3 y; mean duration of illness: 10.7 vs 12.0 y). The MTX+ group included 858 biologic-naïve and 1717 biologic-experienced patients (mean age: 60.6 vs 59.3 y; mean duration of illness: 7.7 vs 10.4 y). The proportion of patients with comorbidities or past medical history between biologic-naïve and -experienced did not differ significantly in MTX+/− groups. The mean MTX dose in biologic-naïve vs -experienced patients was 7.20 vs 7.05 mg/week, respectively. The frequency of adverse drug reactions (ADRs) in biologic-naïve vs -experienced groups were 14.3% vs 17.8%, respectively, in the MTX− group, and 14.6% vs 15.2%, respectively, in the MTX+ group. The corresponding frequency of serious ADRs were 1.2% vs 3.3% (MTX−) and 2.3% vs 2.4% (MTX+). The mean change in DAS28 (CRP) at week 24 in biologic-naïve vs -experienced patients was −1.61 vs −0.93, respectively, in the MTX– group and −1.64 vs −1.08, respectively, in the MTX+ group. Multivariate logistic regression analysis showed that body weight <40 kg, history/presence of respiratory disorders, and concomitant use of prednisolone >5 mg/day were risk factors for serious infections. Steinbrocker's functional class, duration of illness and the number of prior biologics were significant predictors for achieving disease remission or low disease activity. Conclusions: In this 24-week surveillance of ABT-treated patients with RA, biologic-naïve patients experienced fewer serious ADRs and showed greater improvements in disease activity than biologic-experienced patients. References: Koike T, et al. Arthritis Rheum 2013;65(10 Suppl.):S598 Disclosure of Interest: M. Harigai Grant/research support: Abbvie, Astellas, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Santen, Takeda, and UCB, Consultant for: Bristol-Myers, Chugai, Elli-Lilly, and Janssen, Speakers bureau: Abbvie, Astellas, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Takeda, and UCB, N. Ishiguro Grant/research support: Astellas and Bristol-Myers, Consultant for: Abbvie, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, Pfizer, and Takeda, Speakers bureau: Abbvie, Astellas, Bristol-Myers, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, Pfizer, and Takeda, S. Inokuma Speakers bureau: Abbvie, Asahi Kasei Pharma, Astellas, Bristol-Myers, Chugai, Daiichi-Sankyo, Eisai, GlaxoSmithKline, Kyorin, Mitsubishi-Tanabe, Pfizer, Santen, Taiho, Taisho-Toyama, Takeda, and Teijin, T. Mimori Grant/research support: Asahi-Kasei, Astellas, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Santen, and Takeda, Speakers bureau: Bristol-Myers, Chugai, and Mitsubishi-Tanabe, J. Ryu: None declared, Y. Takasaki Grant/research support: Abbvie, Astellas, AstraZeneca, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, and Shionogi, Consultant for: Actelion, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, GlaxoSmithKline, Mitsubishi-Tanabe, Nippon Kayaku, Novartis, Otsuka, Pfizer, Santen, and UCB, Speakers bureau: Abbvie, Actelion, Astellas, Chugai, Daiichi-Sankyo, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, Santen, and UCB, S. Takei Grant/research support: Bristol-Myers, Chugai, Eisai, and Takeda, Speakers bureau: Abbvie, Asahi Kasei, Astellas, Chugai, Eisai, Novartis, Pfizer, Takeda, and Teijin, T. Takeuchi Grant/research support: Abbott, Abbvie, Asahi Kasei, Astellas, Bristol-Myers, Chugai, Daiichi-Sankyo, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, Sanofi-Aventis, Santen, Taisho-Toyama, Takeda, and Teijin, Consultant for: Abbvie, Asahi Kasei, AstraZeneca, Daiichi-Sankyo, Eli Lilly, Mitsubishi-Tanabe, and Novartis, Speakers bureau: Abbott, Astellas, Bristol-Myers, Chugai, Daiichi-Sankyo, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, and Takeda, Y. Tanaka Grant/research support: Abbvie, Astellas, Bristol-Myers, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, and MSD, Consultant for: Abbvie, Actelion, Astellas, AstraZeneca, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, GlaxoSmithKline, Janssen, Mitsubishi-Tanabe, Nippon Kayaku, Novartis, Ono, Otsuka, Pfizer, Quintiles Transnational, Santen, and UCB, Speakers bureau: Abbvie, Actelion, Astellas, AstraZeneca, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, GlaxoSmithKline, Janssen, Mitsubishi-Tanabe, Nippon Kayaku, Otsuka, Pfizer, Quintiles Transnational, Santen, and UCB, H. Yamanaka Grant/research support: Abbvie, Abbott, Astellas, AstraZeneca, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Takeda, and UCB, Consultant for: Abbott, Abbvie, Astellas, AstraZeneca, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Takeda, and UCB, Speakers bureau: Abbott, Abbvie, Astellas, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Takeda, and UCB, M. Watanabe Employee of: Bristol-Myers K.K., T. Koike Speakers bureau: Abbvie, Astellas, Bristol-Myers, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Santen, Taisho-Toyama, Takeda, Teijin, and UCB DOI: 10.1136/annrheumdis-2014-eular.1987